2014
DOI: 10.1111/eje.12084
|View full text |Cite
|
Sign up to set email alerts
|

Implant dentistry education in Europe: 5 years after the Association for Dental Education in Europe consensus report

Abstract: Introduction: To promote consensus on implant dentistry university education in Europe, a workshop amongst university teachers and opinion leaders was organised in 2008. As a result, guidelines on both under-and postgraduate education were issued. This study aims to investigate the current status of university teaching of implant dentistry and the impact of the recommendations for teaching and assessment, 5 years after the first consensus. Finally, this report attempts to identify future directions in educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
67
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(75 citation statements)
references
References 29 publications
7
67
0
1
Order By: Relevance
“…There was a general agreement that the undergraduate education, in the majority of the European countries, does not equip dentists with the clinical skills needed to implement the full spectrum of implant dentistry expected in a modern general practice. This finding is consistent with previous reports , although there has been a recent increase in undergraduates gaining experience in straightforward implant prosthetics . A dental graduate relies on attending CPD courses either to acquire and develop his/her initial core knowledge and skills in implant dentistry or to keep these up to date as part of his/her lifelong learning activity.…”
Section: Discussionsupporting
confidence: 91%
“…There was a general agreement that the undergraduate education, in the majority of the European countries, does not equip dentists with the clinical skills needed to implement the full spectrum of implant dentistry expected in a modern general practice. This finding is consistent with previous reports , although there has been a recent increase in undergraduates gaining experience in straightforward implant prosthetics . A dental graduate relies on attending CPD courses either to acquire and develop his/her initial core knowledge and skills in implant dentistry or to keep these up to date as part of his/her lifelong learning activity.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, a systematic review and a survey on implant dentistry education in Europe have revealed that a substantial number of dental curricula have been fulfilling the 2009 recommendation to include at least limited clinical experience in implant surgery . However, this does not refer to surgical placement of oral implants by undergraduate students, which has not been aspired to by the great majority of institutions.…”
Section: A Undergraduate Educationmentioning
confidence: 99%
“…8 However, in annual surveys of dental school seniors over the past several years, implant dentistry has been one of top areas in which students perceived that the time spent in the curriculum was inadequate. 14 In medical education, Swamy et al found that the transition from didactic training to clinical training was a major source of stress for students. 5,[11][12][13] Initially, implant dentistry training was predominantly didactic in nature.…”
mentioning
confidence: 99%